Network Assessment of a Selected Organization from the Personnel Outsourcing Sector - Rafał TRZASKA (Communications of International Proceedings, 2020)
In the environment displaying more and more characteristics of a network paradigm, enterprises seek solutions helping increase their efficiency. At the same time, strategic management does not offer solutions (methods and techniques) of strategic analysis dedicated to this paradigm. It is a serious scientific problem. Admittedly, methods and techniques borrowed from other disciplines do appear, like the SNA method, but strategic management itself has not prepared its own methods or techniques of network analysis. The aim of this paper is to present a selected method of strategic network analysis. It concentrates on three essential parameters of network assessment. The method comprises: the stricte assessment of the enterprise network, the enterprise strategy assessment in terms of its possession of network characteristics, and the assessment of the environment in which the enterprise operates in terms of network indicators of this environment. The article discusses the structure of the network analysis method in a network approach, with particular emphasis on the following steps: the enterprise network, the network strategy, and the environment in which the enterprise operates. The empirical part presents results of an assessment of an enterprise network, network strategy and environment, using the example of a selected organization from the sector of personnel outsourcing services.
Keywords: Management; Strategic management; Resource Based View; Network assessment.